Use of computed tomography in the diagnosis of caecal inversion in a dog and a cat. Issue 2 (12th May 2019) - Phipps, William Bertram; Mortier, Jeremy Raphael; Booth, Malcolm; Rossanese, Matteo
Abstract : Case 1 : A nine‐month‐old entire male beagle presented with a history of chronic diarrhoea, intermittent haematochezia and rectal prolapse. An exploratory laparotomy performed prior to presentation reported visualisation of a suspected caecocolic intussusception. Physical examination revealed a non‐painful, mid‐abdominal mass and laboratory findings were consistent with non‐specific gastrointestinal disease. Abdominal CT identified intraluminal inversion of the caecum into the ascending colon. Intraoperatively, the inversion was unreducible and a colotomy followed by stapled typhlectomy was performed. Case 2 : An eight‐year‐old neutered male domestic shorthair presented with a history of chronic haematochezia and intermittent partial rectal prolapse. Physical examination and laboratory findings were unremarkable. Abdominal CT revealed a caecal inversion. A midline coeliotomy followed by manual correction of the inversion and a stapled typhlectomy were performed. In both animals, CT allowed an accurate diagnosis and appropriate management of caecal inversion, a rarely reported small animal large intestinal disease.